Pengaruh Intensitas Matahari Terhadap Karakteristik Sel Surya Jenis Polycristaline Menggunakan Regresi Linear - Andi Makkulau; Samsurizal Samsurizal; Miftahul Fikri; christiono Christiono (KILAT, 2021)
Renewable energy sources have both renewable and sustainable properties and the utilization of renewable energy sources is a continuously developed alternative. One of the technologies that can utilize renewable energy is polycrystalline solar cells. Solar cells are technology that converts sunlight energy into electrical energy. This technology is very potentially applied in Indonesia that has a tropical climate, but the main problem of this system is the power instability generated. The power produced relies heavily on the intensity of the sun received by the solar panels. The intensity of the solar radiation received by the solar panels can be maximised by installing solar panels, with a precise tilt angle. In research acquired the relationship between irradiation and current correlates of R = 0.7251. From the correlation value above indicates that there is a strong link and is directly proportional between irradiation and the current obtained. The acquired Model needs to be seen its accuracy, in which case it will be used Mean Absolute Percent Error So it is obtained by 26.5%. This indicates that the model is good enough.